Parametrization and Applications of Precoding Reuse and Downlink Interference Alignment - Castañeda, E.
In this paper, we consider the downlink communication of an arbitrary number of transmitters over broadcast interference channels. In order to suppress interference, we investigate a network-level linear precoding scheme dubbed precoding reuse. Such a technique is leveraged on the interference alignment (IA) principle, where the undesired signals overlap in a reduced-dimension subspace at the receivers. Precoding reuse relies on two cascaded precoders to suppress intra- and inter-cell interference and requires feedback only within a cell. We designed precoding reuse schemes for which interference suppression can be attained in a coordinated or uncoordinated fashion over a fixed number of quasi-static channel uses. We provide expressions for the parametrization of the precoders and investigate the advantages, limitations, suitable scenarios, and applications of the proposed IA scheme. Finally, we pointed out the open problems, where the proposed IA scheme and parametrization can be implemented with little effort, demanding minimum changes to an existing cellular system supporting multi-user MIMO.